Fatigue Behavior of Hybrid Components Containing Maraging Steel Parts Produced by Laser Powder Bed Fusion - Santos, Luís (2021)
This investigation concerns about of fatigue behavior under controlled loading and under strain control for hybrid specimens with parts produced with conventional processes in steel AISI H13 and the stainless steel AISI 420 and the rest part produced by laser powder bed fusion in AISI 18Ni300 steel. The controlled loading tests were performed in constant and variable amplitude. Fatigue failure of hybrid samples occurs mostly in laser-melted parts, initiated around the surface, in many cases with multi-nucleation and propagated predominantly between the deposited layers. Fatigue strength of hybrid parts, tested under displacement control is similar, but for specimens tested under load control the fatigue strength the fatigue strength of hybrid specimens is progressively lesser than laser powder bed fusion samples. Despite a tendency to obtain conservative predictions, Miner’s law predicts reasonably the fatigue lives under block loadings. The interface between materials presented an excellent joining and fatigue strength because the fatigue failure of hybrid samples occurred mostly in laser melted parts out of the interface.